Effective interactions in protein-salt solutions approaching liquid-liquid phase separation - Wolf, M; Roosen-Runge, F; Zhang, F; Roth, R; Skoda, M; Jacobs, R; Sztucki, M; Schreiber, F (Elsevier, 2014)
We present an experimental study combined with a theoretical discussion of the effective interactions in protein solutions approaching a liquid-liquid phase separation (LLPS) induced by addition of multivalent metal ions. The reduced second virial coefficient, B2/B2HS, is used to describe the interaction and discussed with theoretical predictions for colloidal systems. We have determined the salt and protein partitioning in the two coexisting phases, which provides the isothermal binodal of the LLPS in the (cp, cs) plane. Two sets of samples, away from and at the LLPS binodal were measured by static light scattering (SLS) and small angle X-ray scattering (SAXS) to determine the second virial coefficient. In all cases, B2/B2HS is negative in the condensed regime, and increases by approaching the upper critical point in the (cp, cs) plane. The results are compared with a simple colloidal model with isotropic short-ranged attraction and a thermodynamic criterion based on the reduced second virial coefficient. We discuss the application of this theoretical prediction to interpret experimental observations.